2022
DOI: 10.1111/rode.12867
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global value chains on total factor productivity: The case of Indian manufacturing

Abstract: With production increasingly fragmented across borders, global value chains (GVCs) form a key feature of the world economy. A rising body of literature has documented productivity gains from linking into GVCs for developed-country firms, but studies on the same for developing countries are scant. In this paper, we empirically examine whether GVCs can increase total factor productivity (TFP) in developing countries, using an unbalanced panel of Indian manufacturing firms in the period 2000/2001-2014/2015 from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Strengthening manufacturing servitization and service trade openness in middle-and lowincome countries can help them achieve economic diversification, increase their service value added, and improve their manufacturing productivity by promoting knowledge transfer, operational efficiency, and customer-centric approaches (Grover & Mattoo, 2021). This is supported by recent empirical evidence that linking into global value chains has a positive and significant impact on firm TFP in developing countries, particularly in Indian manufacturing firms (Banga, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…Strengthening manufacturing servitization and service trade openness in middle-and lowincome countries can help them achieve economic diversification, increase their service value added, and improve their manufacturing productivity by promoting knowledge transfer, operational efficiency, and customer-centric approaches (Grover & Mattoo, 2021). This is supported by recent empirical evidence that linking into global value chains has a positive and significant impact on firm TFP in developing countries, particularly in Indian manufacturing firms (Banga, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…Li et al (2023) used "Energy-Environmental-Economic" (3E) system to examine the relationship between the digital economy and 3E efficiency in EU countries, and they found that in terms of the relationship between the digital economy and 3E efficiency, the digital economy has direct and indirect (through economic growth) impacts on 3E efficiency; when GDP per capita exceeds EUR 15,580, the influence coefficient of the digital economy on 3E efficiency changes from negative to positive [14]. The digital economy accelerates the upgrading of traditional industrial infrastructure, promotes the construction of digital infrastructure, and then realizes the digital upgrade of traditional industries and improves the efficiency of industrial development [15]. The analysis of property rights theory and transaction cost theory from new institutional economics; and the research on changes in innovation subjects, technologies, and behavioral approaches from innovation theory [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital infrastructure, digital industrialization, and industrial digitalization are agreed upon by researchers as major indexes measuring the digital economy [16]. The digital economy leads to faster infrastructure upgrading in traditional industries and several digital infrastructures, thus digitalizing these industries to make industry development more efficient [15]. Digital infrastructure lifts the productivity of production factors, which improves industrial divi-sion and specialization to optimize industrial structure and causes a knowledge spillover effect [26].…”
Section: Research Hypothesismentioning
confidence: 99%
“…cooperative membership) on binary outcome variables (adoption of physical or biological pest control practices), several econometric methods could be used to correct for selection bias. These include the propensity score matching (PSM; Banga, 2022; Shimada & Sonobe, 2021), inverse‐probability weighted regression adjustment (IPWRA) estimator (Manda et al, 2018; Zheng & Ma, 2021), recursive bivariate probit (RBP) model (Li, Cheng, & Shi, 2021; Owusu et al, 2021; Zheng et al, 2021) and the endogenous switching probit (ESP) model (Haile et al, 2020; Li et al, 2020). This study employs the ESP model for two reasons.…”
Section: Background and Econometric Strategymentioning
confidence: 99%